INTEGRASI PEMBENTUKAN KARAKTER DALAM PEMBELAJARAN IPS SD - Arni Gemilang Harsanti (Universitas PGRI Madiun, 2015)
The ministry of national education (kemendiknas) stated the application ofcharacter education in every level from Elementary School to University. It isbecause during these days, educational world scored less succeed in introducingnational generation to become prestige personality. It is implicated through everysubject of study, like social studies. The position of social studies learning is sounique because there must be preparation to educate students to live andunderstand their world, where their personal and social quality will become moreimportant. The developed values in character education are identified by: (1)religion, (2) Pancasila, (3) Cultural, and (4) National education purposes. Thevalue of social studies, a teacher must push the students to become active inobtaining values. Through social studies, students are directed to be democraticand responsible citizen and also world citizen who love peaceful. The subject ofsocial studies is designed to develop science, understanding and analysis abilityto social community condition in entering dynamic society life.